The impact of periampullary diverticula on the endoscopic treatment of choledocholithiasis - Aslan, Fatih; Arabul, Mahmut; Alper, Emrah; Celik, Mustafa; Kandemir, Altay; Unsal, Belkis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Introduction : Periampullary diverticula (PD) are generally asymptomatic and frequently diagnosed coincidentally during endoscopic retrograde cholangiopancreatography (ERCP). Aim : To investigate the impact of PD on procedural success in ERCP for common bile duct (CBD) stones, and possible complications. Material and methods: Five hundred and eighty-six patients diagnosed with CBD stones by diagnostic techniques and treated by ERCP were prospectively included in the study. Periampullary diverticula presence (patients with PD were allocated to group A, and those without PD to group B), size of the diverticulum (< 2 cm or  2 cm), papillary association with the diverticulum, size and number of CBD stones, were prospectively recorded for each patient. Total extraction of CBD stones by ERCP was considered successful treatment, and inability to remove the stone(s) was defined as lack of success. Results : Group A consisted of 478 (82%), and group B 108 patients (18%). Cannulation success at first try was 97.7% in group A, and 95.4% in group B patients (p > 0.05). The prevalence of stone impaction was 3.1% in group A, and 10.2% in group B (p < 0.01). 86.8% of group A and 81.5% of group B patients were treated endoscopically. Conclusions : Periampullary diverticula is a contributing factor in the formation of choledocholithiasis, and in the increase in size or impaction of existing stones. However, the presence of PD does not necessarily affect the success of ERCP or the prevalence of procedure-related complications in patients with CBD stones.